2019
DOI: 10.3389/fphar.2019.01193
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy in Hepatic Insulin Resistance: Therapeutic Potential and Concerns

Abstract: Metabolic syndrome, characterized by central obesity, hypertension, and hyperlipidemia, increases the morbidity and mortality of cardiovascular disease, type 2 diabetes, nonalcoholic fatty liver disease, and other metabolic diseases. It is well known that insulin resistance, especially hepatic insulin resistance, is a risk factor for metabolic syndrome. Current research has shown that hepatic fatty acid accumulation can cause hepatic insulin resistance through increased gluconeogenesis, lipogenesis, chronic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 181 publications
(231 reference statements)
1
37
0
Order By: Relevance
“…Importantly, in the liver, insulin resistance originating from lipotoxicity has no link with impaired mitochondrial capacity, which has been attributed to a mitochondrial adaptation to promote increased lipolysis (Jelenik et al., 2017). More recent literature has highlighted the role of mitophagy in promoting mitochondrial fatty acid oxidation, as a consequence reducing hepatic fatty acid accumulation, leading to improved hepatic insulin resistance (Su et al., 2019). Studies showed that hepatic fatty acid accumulation resulted in an increase in the accumulation of damaged mitochondria (Wu et al., 2015); however, PINK1/Parking‐mediated mitophagy could reverse this phenomenon (Nguyen et al., 2016; Wang et al., 2019).…”
Section: Livermentioning
confidence: 99%
“…Importantly, in the liver, insulin resistance originating from lipotoxicity has no link with impaired mitochondrial capacity, which has been attributed to a mitochondrial adaptation to promote increased lipolysis (Jelenik et al., 2017). More recent literature has highlighted the role of mitophagy in promoting mitochondrial fatty acid oxidation, as a consequence reducing hepatic fatty acid accumulation, leading to improved hepatic insulin resistance (Su et al., 2019). Studies showed that hepatic fatty acid accumulation resulted in an increase in the accumulation of damaged mitochondria (Wu et al., 2015); however, PINK1/Parking‐mediated mitophagy could reverse this phenomenon (Nguyen et al., 2016; Wang et al., 2019).…”
Section: Livermentioning
confidence: 99%
“…While obesity is associated with chronic inflammation that leads to insulin resistance and NAFLD [90], mitochondrial dysfunction is involved in all three metabolic disorders [102][103][104][105]. Most notably, mitochondrial defects in FAO lead to the accumulation of intracellular fatty acid metabolites such as dihydroxyglycerol and ceramides that adversely affect insulin signaling in various tissues [106][107][108]. Similarly, many of the genes that are regulated by transcription factors and NRs also play a critical role in the development of insulin resistance [109,110].…”
Section: Esrra As a Target For Insulin Resistance And Type 2 Diabetesmentioning
confidence: 99%
“…Autophagy is considered to play an important role in the pathogenesis of various diseases (Doherty and Baehrecke, 2018 ). Increasing evidence shows that autophagy can regulate many key functions of the kidney in the normal and diseased state (Su et al, 2019 ; Zhang et al, 2020 ). STZ-induced autophagy is inhibited in the proximal and early tubules of DM rats, which is associated with renal tubular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%